Reconstructed Bismuth-Based Metal-Organic Framework Nanofibers for Selective CO2 -to-Formate Conversion: Morphology Engineering - Ying, Yulong; Khezri, Bahareh; Kosina, Jiri; Pumera, Martin (ChemSusChem, 2021)
Electrochemical reduction of carbon dioxide (ERCO2 ) is an attractive and sustainable approach to close the carbon loop. Formic acid is a high-value and readily collectible liquid product. However, the current reaction selectivity remains unsatisfactory. In this study, the bismuth-containing metal-organic framework CAU-17, with morphological variants of hexagonal prisms (CAU-17-hp) and nanofibers (CAU-17-fiber), is prepared at room temperature through a wet-chemical approach and employed as the electrocatalyst for highly selective CO2 -to-formate conversion. An H3 BTC-mediated morphology reconstruction is systematically investigated and further used to build a CAU-17-fiber hierarchical structure. The as-prepared CAU-17-fiber_400 electrodes give the best electrocatalytic performance in selective and efficient formate production with FEHCOO- of 96.4 % and jCOOH- of 20.4 mA cm-2 at -0.9 VRHE . This work provides a new mild approach for synthesis and morphology engineering of CAU-17 and demonstrates the efficacy of morphology engineering in regulating the accessible surface area and promoting the activity of MOF-based materials for ERCO2 .
Keywords: electrocatalysis; formic acid; carbon dioxide; morphology engineering; metal−organic frameworks